Toxicological, chemopreventive, and cytotoxic potentialities of rare vegetal species and supporting findings for the Brazilian Unified Health System (SUS). Issue 13 (17th July 2020) - Silva, Jurandy do Nascimento; Monção, Nayana Bruna Nery; de Farias, Ruth Raquel Soares; Citó, Antonia Maria das Graças Lopes; Chaves, Mariana Helena; Araújo, Mônica Regina Silva de; Lima, Daisy Jereissati Barbosa; Pessoa, Claudia; Lima, Alessandro de; Araújo, Edigênia Cavalcante da Cruz; Militão, Gardenia Carmen Gadelha; Costa, Marcília Pinheiro da; et al.
ABSTRACT: Caatinga flora which are found in a poor Brazilian region contain a substantial number of endemic taxa with biomedical and social importance for regional communities. This study examined the antioxidant and cytotoxic potential of 35 samples (extracts/fractions) from 12 Caatinga species and determined the antiproliferative and genotoxic action of dichloromethane fraction from Mimosa caesalpiniifolia stem bark (DC-Mca) on human and vegetal cells. Samples were assessed for chemopreventive ability, toxic effects on Artemia salina shrimp as well as cytotoxicity on tumor cell lines and erythrocytes. DC-Mca was also tested with respect to antiproliferative and genotoxic effects upon normal leukocytes and meristematic cells from A. cepa roots. Some extracts reduced free radical levels >95% and 7 samples exhibited a lethal concentration (LC) 50  < 100 µg/ml upon Artemia salina larvae. Eight samples displayed in vitro antitumor effects and three produced hemolysis. Data also demonstrated the pharmacological significance of bioactive extracts from Brazilian semi-arid region. There was no significant relationship between antioxidant, toxic, and antiproliferative activities, and that these properties were dependent upon the extractant. DC-Mca contained betulinic acid as main compound (approximately 70%), which showed higher (1) cytotoxic activity on cancer cell lines and dividing leukocytes, (2) reduced mitotic index of Allium cepa roots, and (3) induced cell cycle arrest and chromosomal bridges, thereby providing native promising sources for phytotherapy development. Abbreviations: ABTS: 2, 2ʹ-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid); AcOH: ethyl acetate; ANOVA: analysis of variance; SUS: Brazilian Unified Health System; DC-Mca: dichloromethane fraction from Mimosa caesalpiniifolia stem bark; DMSO: dimethylsulfoxide; DPPH: 1, 1-diphenyl-2-picrylhydrazyl; EC50 : effective concentration 50%; EtOAc: ethyl acetate; FDA: Food and Drug Administration; GC-Qms: gas chromatograph quadrupole mass spectrometer; GI: genotoxic index; HCT-116: colon carcinoma line; HL-60: promyelocytic leukemia line; HPLC: high-performance liquid chromatography; HRAPCIMS: high resolution atmospheric pressure chemical ionization mass spectrum; IC50 : inhibitory concentration 50%; LC50 : lethal concentration 50%; MeOH = methyl alcohol; MI: mitotic index; MTT: 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2H-tetrazolium bromide; MutI: mutagenic index; OVCAR-8 = ovarian carcinoma line; PBMC: peripheral blood mononuclear cells; RPMI-1640: Roswell Park Memorial Institute medium; SF-295: glioblastoma line; TEAC: trolox equivalent antioxidant capacity; TLC: thin-layer chromatography; Trolox: 6-hydroxy-2, 5, 7, 8-tetramethylchroman-2-carboxylic acid